Sekakoivikon reaktio ensiharvennukseen mustikkaturvekankaalla Lapissa - Hökkä, Hannu; Penttilä, Timo (Helsinki : Suoseura, 1995)
Summary: Thinning response of a young, birch-dominated mixed stand on Vaccinum myrtillus peatland forest type in Lapland